1996
DOI: 10.1108/02641619610155102
|View full text |Cite
|
Sign up to set email alerts
|

Serial cuts and interlibrary loan: filling the gaps

Abstract: The Southern Illinois University at Carbondale (SIUC) Library, which is a member of the Association of Research Libraries with holdings exceeding 2,000,000 volumes and current serial subscriptions numbering more than 14,000, intended to serve a constituency of 25,000 graduate and undergraduate students and 5,000 faculty and staff. Documents how in fiscal year 1990, financial exigency resulted in the cancellation of 1,241 serial titles at the library for a saving of US$233,322.80. Describes how a review of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Bryson (1999), Fishwick (1986 and Kilpatrick and Preece (1996) agree that LIS are vulnerable to variations in exchange and inflation rates, evidenced by price rises at present being amplified by the declining value of the pound sterling (Greco et al, 2007; Scholarly Communications Report, 2008;Taylor-Roe, 2009). Another niche problem is the value added tax (VAT) charge on all electronic resources in the UK (Taylor-Roe, 2000).…”
Section: Collection Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Bryson (1999), Fishwick (1986 and Kilpatrick and Preece (1996) agree that LIS are vulnerable to variations in exchange and inflation rates, evidenced by price rises at present being amplified by the declining value of the pound sterling (Greco et al, 2007; Scholarly Communications Report, 2008;Taylor-Roe, 2009). Another niche problem is the value added tax (VAT) charge on all electronic resources in the UK (Taylor-Roe, 2000).…”
Section: Collection Managementmentioning
confidence: 99%
“…This is a serious issue for LIS in HE as serials expenditure is a major proportion (60-80%) of their materials budget and is a continuous budgetary commitment (Greco et al, 2007;Taylor-Roe, 2000). The high cost of serials can lead to decisions to cancel subscriptions (Kilpatrick and Preece, 1996).…”
Section: Collection Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Edward Warner's 1981 study showed that faculty considered ILL an effective method for cost control combined with access to content. Studies throughout the 1990s repeatedly showed that journal cancellation projects resulted in negligible increase in ILL demand both shortly after the cancellations and in the long term (Crump & Freund, 1995;Kilpatrick & Preece, 1996;Wilson & Alexander, 1999). No recent research was found, but anecdotal evidence suggests that increased ILL demand remains a concern when undertaking journal cancellation projects.…”
mentioning
confidence: 99%